Ill-Gotten Contracts in New Zealand: Parting Thoughts on Duress, Undue Influence and Unconscionable Dealing – Kiwi-Style? - Bigwood, Rick (Victoria University of Wellington Law Review, 2011)
This article considers the private-law doctrines of duress, undue influence and unconscionable dealing as they have feared at the hands of New Zealand’s judiciary. It speculates, necessarily briefly, on whether there is anything distinctively "Kiwi" about the courts’ formulation of and approach to those three doctrines in New Zealand, whether individually or as a related set. It concludes that because New Zealand’s courts have borrowed from different, and not entirely consistent, jurisprudential sources of inspiration in relation to the development of each of the subject doctrines, what has resulted is a suite of exculpatory doctrines that are not as intellectually coordinated as they could and should be.